Autism and Pervasive Developmental Disorders - Volkmar, Fred R. (Cambridge University Press, 2019)
Interest in autism and related disorders has exploded. Established as an essential book on this complex syndrome, the new edition has been extensively revised to reflect significant advances in research. Featuring contributions from leading international authorities in the clinical and social sciences, the book covers recent progress in our understanding of the field and offers a perspective on the present state of the discipline. With new material on topics such as evidence-based treatment and practice, the book covers changes in diagnosis resulting from the publication of DSM-V, and developments in how autism is understood, including the removal of language delay as a necessary diagnostic criterion. Far-reaching, the book considers aspects from epidemiology, genetics, and neurobiology, to core symptoms, early interventions, and pharmacology. One section critically surveys the history of autism as a diagnostic concept, and issues such as an ageing population and the impact of research on national policy are considered.
Keywords: dept.sed